John C. Poirier - Jeffrey Peterson (ed.), Marcan Priority without Q. Explorations in the Farrer Hypothesis (Library of New Testament Studies 455; London - New York: Bloomsbury - T&T Clark 2015) - Adamczewski, Bartosz (The Biblical Annals, 2016)
Book review: John C. Poirier - Jeffrey Peterson (ed.), Marcan Priority without Q: Explorations in the Farrer Hypothesis (Library of New Testament Studies 455; London - New York: Bloomsbury - T&T Clark 2015). Pp. XIV + 272. 110,00. ISBN 978-0-56715 -913-7.